2007
DOI: 10.1007/s11104-007-9512-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phosphorus fractions in the rhizosphere of common bean (Phaseolus vulgaris L.) and durum wheat (Triticum turgidum durum L.) grown in monocropping and intercropping systems

Abstract: The main objective of the present study was to investigate phosphorus (P) dynamics in the rhizosphere of durum wheat (Triticum turgidum durum L.) and common bean (Phaseolus vulgaris L.) grown in monocropping and intercropping systems with nitrate supply. Wheat and common bean were grown either alone or in association in a cropping device with a thin (1 mm) soil layer sandwiched between large root mats. Wheat intercropped with common bean exhibited a 33% increase in shoot biomass and a 22% increased root biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
87
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 62 publications
14
87
1
6
Order By: Relevance
“…Biochemical niche complementarity can occur when two intercropped species tap into different pools of soil P (Fig. 1), such as inorganic and organic pools (Li et al, 2008), or different chemical forms of each of these pools (Turner, 2008;Wang et al, 2012). Wheat and associated white lupin plants in mixed culture were shown to deplete water-extractable and citric-acidextractable inorganic P fractions in a low-P soil (four parts washed sand, one part garden soil), respectively (Cu et al, 2005).…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical niche complementarity can occur when two intercropped species tap into different pools of soil P (Fig. 1), such as inorganic and organic pools (Li et al, 2008), or different chemical forms of each of these pools (Turner, 2008;Wang et al, 2012). Wheat and associated white lupin plants in mixed culture were shown to deplete water-extractable and citric-acidextractable inorganic P fractions in a low-P soil (four parts washed sand, one part garden soil), respectively (Cu et al, 2005).…”
Section: Observationsmentioning
confidence: 99%
“…Increased N 2 fixation in legumes as a consequence of competition of cereals for nitrate further stimulates P acquisition (Hinsinger et al, 2011). Several experiments have shown a lower rhizosphere pH for legumes than cereals, while pH values in the rhizospheres of cereal-legume mixtures have been found to be intermediate (Li et al, 2003a;Cu et al, 2005;Li et al, 2008). In addition, not only proton excretion and hence rhizosphere acidification but also reduced N 2 fixation and release of hydroxyl ions and consequent increase in rhizosphere pH can raise P availability in the rhizosphere of durum wheat and chickpea in a P-limited neutral soil (Betencourt et al, 2012).…”
Section: Interspecific Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the effects of soil management systems are preponderant on the soil acidity attributes compared to the cultivation of different cover crops. In fact, the effects of cultivation of different plants on soil acidity attributes are most frequently determined at rhizosphere level (Li et al, 2008). As we did not evaluate the rhizosphere soil, but the bulk soil, it is possible that the winter cover crops effect on soil acidity attributes may have been diluted.…”
Section: Effect Of Tillage System and Winter Treatments On Soil Acidimentioning
confidence: 99%
“…Furthermore, Wang et al (2008) reported that the acquisition of phosphate in low availability conditions was improved by the release of protons by wheat. Li et al (2008) showed that common bean decreased the rhizosphere pH by 1.66 units reducing also the available P-resin to 43% of the no-plant control soil. Many factors contribute to this pH change, including the imbalance in cation-anion uptake, particularly affected by nitrogen sources, and increased efflux of protons as a result of P deficiency (Gahoonia and Nielsen, 2004).…”
Section: Introductionmentioning
confidence: 98%